Interactions between dark septate endophytes, ectomycorrhizal fungi and root pathogens in vitro. Issue 13 (11th July 2019) - Berthelot, Charlotte; Leyval, Corinne; Chalot, Michel; Blaudez, Damien
ABSTRACT: Dark septate endophytes (DSEs) are widely distributed worldwide and can promote plant growth. Therefore, they are considered potentially important plant allies, especially in stressful environments. Previous studies have reported that DSEs cohabit roots with other microorganisms such as ectomycorrhizal (ECM), endophytic and pathogenic fungi/oomycetes. However, interactions between different DSE species have not yet been reported, and studies on the interactions between DSEs and other fungi are scarce. Using a simple and reproducible pairwise growth assay in vitro, we studied the synergistic/antagonistic interactions between eight DSEs, two ECM fungi and three root pathogens. Most of the DSE/DSE outcomes were neutral. Interestingly, we identified several DSE strains acting in synergy with other strains, as well as strains that could potentially act as biocontrol agents. Notably, three metal-tolerant DSE strains, namely, Cadophora sp., Leptodontidium sp. and Phialophora mustea, could decrease the growth of the root phytopathogens Pythium intermedium, Phytophthora citricola and Heterobasidion annosum . The present data are discussed in the general context of the use of fungal consortia as inocula in the tree-based phytomanagement of marginal lands. Abstract : Interactions of dark septate endophytes (DSEs) with other root-inhabiting fungi: most of the strains show antagonistic effects on phytopathogens but not on other DSEs.